The Effect of Skipping Exercise on Endurance Level among Adolescents aged 15-18 years in Gribin Volleyball Community Surabaya - Raudah, Quds; Meilani, Estu; Wardani, Nurul Kusuma (Jurnal Ilmu-Ilmu Kesehatan, 2025)
Background: The most frequently encountered problem of individuals who are in transition period from childhood to adulthood is deteriorated cardiorespiratory endurance due to low physical activity. Adolescents had low physical activity because of their sedentary lifestyle. The exercise that could boost their cardiorespiratory endurance is long duration exercise with moderate intensity, such as skipping exercise. Objectives: This study aimed to evaluate the effect of skipping exercise on the endurance level of adolescents age 15-18 years in Gribin Volleyball Community, Surabaya. Methods: This study utilized an experimental analytics method with pre-test and post-test with control group design. The sample consisted of members Gribin Volleyball Community Surabaya aged 15-18 years. The endurance level was evaluated using PACER test, then the data was analyzed using Shapiro-Wilk test for normality prior to the next analysis. Then, in order to compare the data in-between and between groups, Paired T-test, Wilcoxon Signed Rank test, and Mann-Whitney U test were performed. Results: The mean of post-test VO2Max in the control group was 20.80 ± 0.94 ml/kg/min, while the mean of post-test VO2Max in the intervention group was 23.64 ± 1.85 ml/kg/min. The Mann-Whitney U test results showed a significant different of the post-test VO2Max between group with p-value of 0.000 (P<0.05). Conclusion: The skipping exercise had a significant effect on improving endurance level among adolescents age 15-18 years in Gribin Volleyball Community, Surabaya. Keywords: adolescent, endurance, skipping exercise, PACER test